Law, the state, and the dialectics of state crime - Ward, Tony (Critical criminology, 2016)
Drawing on material from a study of civil society and state crime in six countries, this article reflects on two themes from Chambliss’s work: the debate between state-centred and more pluralistic views of law, and the "dialectical" approach to the analysis of state crime. It argues for a more pluralistic approach to law than Chambliss and Seidman adopted in Law Order and Power, along with a broader approach to the definition of state crime as a form of deviant behaviour. Case studies from the civil society research illustrate how the strategies adopted by organizations challenging state practices can be understood in terms of an interplay between different forms of law. With some qualifications, we support Chambliss’s dialectical approach, and attempt to clarify just what the term "dialectical" means. Finally we bring together the two strands of the argument to propose an approach to state crime founded on "dialectical legal pluralism".